New Horizons in African Finance : Reducing Risk and Mobilizing Financing on a New Scale - International Finance Corporation (Washington, D.C., 2017)
Africa is a region with enormous potential for private investors. It is a continent in transition, with rapid urbanization, increasingstability, a young and growing population, expanding internet connectivity, rising incomes, and shifting consumption patterns. Taken together, these enduring trends have created an abundance of commercial opportunities across the continent and turned the region into a place that investors cannot afford to ignore. Yet declining commodity prices, depreciating currencies and slowing global growth have increased uncertainty on the continent and sharply reduced liquidity that companies had used to expand activities in recent years. Economies face a significant challenge to diversify and export a wider range of goods and services.Even before recent global economic turmoil emerged, investor activity in Africa was constrained by structural obstacles and a lack of financing options that often inhibited the effective distribution and mitigation of risk associated with large-scale or long-term projects. Fortunately, companies looking to seize still significant opportunities in Africa can benefit from additional sources of financing, as well as tools that crowd in more private sector participants and mitigate risk, spreading it among different investor classes and over longer timeframes. Tools such as blended finance, co-financing, local debt and equity instruments, private equity, and public-private partnerships are being deployed in Africa in new ways that address risks associated with low-income and fragile states. They provide innovative paths to securing financing on a scale that can match the scope of business opportunities and help manage risk in high-growthAfrican markets.